2009
DOI: 10.1590/s0103-166x2009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Análise funcional como estratégia para a tomada de decisão em psicoterapia infantil

Abstract: Este artigo apresenta a sistematização dos dados provenientes da condução de um processo psicoterapêutico infantil, a partir do modelo de análise funcional descritiva proposto por Sturmey, 1996. O trabalho apresenta a descrição do caso, a avaliação realizada, as análises funcionais de cada etapa da intervenção, os objetivos e estratégias de tratamento, selecionadas com base nas análises realizadas, e os resultados obtidos. Discute-se, a partir da sistematização apresentada, qual a contribuição da análise funci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Item 11, "Demonstrates comprehension of the reason(s) for being in psychotherapy" was considered by the participants of the cognitive-behavioral approach as very relevant, which supports the theoretical premise that the progress would be related to the possibility of understanding, by the patients, that they have difficulties and that they need to actively collaborate to face them (Bandura, 1986(Bandura, /2008Moura, Grossi, & Hirata, 2009). This same item was considered moderately relevant by the psychodynamic therapists, probably due to the relevance they attach to the unconscious aspects of the personality (Romanowski, 2004;Yanof, 2005).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Item 11, "Demonstrates comprehension of the reason(s) for being in psychotherapy" was considered by the participants of the cognitive-behavioral approach as very relevant, which supports the theoretical premise that the progress would be related to the possibility of understanding, by the patients, that they have difficulties and that they need to actively collaborate to face them (Bandura, 1986(Bandura, /2008Moura, Grossi, & Hirata, 2009). This same item was considered moderately relevant by the psychodynamic therapists, probably due to the relevance they attach to the unconscious aspects of the personality (Romanowski, 2004;Yanof, 2005).…”
Section: Discussionmentioning
confidence: 71%
“…For all the approaches, it is indispensable that the children express themselves according to their development and that the form of this expression occurs through play, which will gradually change (Moura et al, 2009). Thus, it is concluded that despite the theoretical differences value was given to: the playful expression, the autonomy, and the tolerance of frustration always in a climate of trust that is established through affective communication with the therapist.…”
Section: Discussionmentioning
confidence: 99%
“…Nos artigos analisados, visualiza-se que as intervenções no âmbito clínico diferem no que diz respeito às abordagens teóricas. Observa-se ainda que, da amplitude de teorias, os desenvolvimentos técnicos fundamentam-se principalmente na visão de homem das perspectivas (Moura et al, 2009;Gastaud, Carvalho, Goodman, & Ramires, 2015;Nadir, Hansel & Guillermo, 2016).…”
Section: Métodounclassified